The influence of dietary choices: investigation of the relationship dietary inflammatory index and fetal growth restriction - Ayşe Gülçin Baştemur; İclal Sena Gezer; Burcu Kesikli; Atakan Tanaçan; Özgür Kara; Nuray Yazıhan; Dilek Şahin (BMC Pregnancy and Childbirth)
Abstract Background Fetal growth restriction (FGR) is characterized by the fetus’s inability to reach its growth potential and affecting approximately 10% of the population. The etiology of late-onset FGR, which occurs after 32 weeks, is unclear but may be influenced by maternal weight. A proinflammatory diet can cause chronic inflammation and, Dietary Inflammatory Index (DII) was developed to evaluate of the diet’s impact on inflammation. A high DII indicates a pro-inflammatory diet, known to increase serum inflammatory markers, with oxidative stress playing a key role in inflammatory diseases. The study aimed to investigate the correlation between maternal DII, total oxidant status (TOS), total antioxidant status (TAS), interleukin-6 (IL-6), interleukin-10 (IL-10), and tumor necrosis factor-alpha (TNF-α) levels in FGR-diagnosed pregnant women. Methods This prospective-observational study included FGR-diagnosed pregnant women and healthy pregnant women with gestational ages of 32–38 weeks (n = 23 per group). Chronic diseases, hypertension, fetal anomalies, membrane ruptures, and multiple pregnancies were excluded. The DII was calculated using the BeBiS-9 program based on 3-day dietary records kept by an expert dietician. Blood samples were collected, centrifuged, and analyzed for IL-6, TNF-α, IL-10, TAS, and TOS. Results The study group had significantly higher DII scores (p < 0.001), lower energy (p = 0.004), carbohydrate (p = 0.002), protein (p = 0.011), fiber (p < 0.001) intake than the control group. TNF-α levels were elevated in the FGR group (p < 0.001), while IL-6 levels were higher but not statistically significant (p = 0.06). IL-10 levels were lower in the study group (p = 0.05). TAS, TOS, and TAS/TOS levels showed no significant differences between groups. Logistic regression indicated a 62% increase in FGR probability with higher DII levels (p = 0.001, CI 1.209–2.195). Correlation analysis revealed a strong positive correlation between DII and maternal serum TNF-α (r = 0.375, p = 0.01) and a strong negative correlation between birth weight and TNF-α (r=-0.478, p < 0.001) and DII (r=-0.446, p = 0.002). Conclusion This study showed that a pro-inflammatory maternal diet increased dietary inflammatory index and increased maternal inflammatory markers, and this was more significant in fetuses with FGR than in normal weight fetuses.